Implementation of a Kidney Genetic Service Into the Diagnostic Pathway for Patients With Chronic Kidney Disease in Canada - Clara Schott; Monica Arnaldi; Cadence Baker; Jian Wang; Adam D. McIntyre; Samantha Colaiacovo; Sydney Relouw; Gabriela Almada Offerni; Carla Campagnolo; Logan R. Van Nynatten; Ava Pourtousi; Alexa Drago-Catalfo; et al. (Kidney International Reports)
Introduction: Genetic kidney disease (GKD) accounts for 10% to 20% of chronic kidney disease (CKD). Genetic testing using gene panel or targeted exome sequencing (ES) can confirm GKD; however, integration into clinical practice has been hampered by small studies, selective populations, and data predominately derived from research settings. Using prespecified clinical referral criteria and a diagnostic pipeline, we performed a prospective cohort study describing diagnostic efficacy and clinical utility of genetic assessment in patients with CKD. Methods: We analyzed a prospective cohort of 300 participants (256 families) referred to a kidney genetics clinic, between March 2020 and March 2024. Testing strategies included gene panels, and if negative or unsuitable, targeted ES analysis. Testing was performed for the detection of variants in genes known to cause CKD. Results: We identified a causative variant in 33% of families (85/256). Diagnostic yield increased from 23% (n = 70/300) from gene panel alone, to 34% (n = 103/300) with comprehensive testing. The median time from first diagnosis of CKD to genetic assessment was long at 10.4 years. Following genetic assessment, the median time to receive a positive genetic result was 2.9 months. Multiple levels of clinical utility were recorded in patients receiving a genetic diagnosis, varying across CKD subtype. Conclusion: Instituting referral guidelines and a standardized testing algorithm established a genetic diagnosis in one-third of participants, providing insight into the viability of integrating genetic assessment in the CKD diagnostic pathway. Considering the potential for clinical utility, strategies to reduce the time from CKD diagnosis to genetics assessment are needed.